The witness wore red : the 19th wife who brought polygamous cult leaders to justice - Musser, Rebecca; Cook, M. Bridget (Grand Central Publishing, 2013)
A gripping account of Rebecca Musser's struggle to escape the Fundamentalist Church of Jesus Christ of Latter Day Saints led by Rulon Jeffs and his son, Warren, and her subsequent decision to take the witness stand against the new prophet of the FLDS in order to protect her little sisters and other young girls from being forced to marry at shockingly young ages.